Economic growth and welfare of the population of the Republic of Uzbekistan (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article examines the interplay between economic growth and welfare outcomes in the Republic of Uzbekistan. Against a backdrop of economic reforms and strategic initiatives, Uzbekistan has experienced notable advancements in sectors such as agriculture, industry, and infrastructure. These developments have contributed to improved living standards and socio-economic conditions for its population. The article analyzes key factors driving economic growth, including investment in human capital, expansion of trade relationships, and reforms aimed at enhancing business environment and governance. Additionally, it discusses challenges and opportunities in sustaining economic momentum while ensuring equitable distribution of benefits across society. Ultimately, Uzbekistan's trajectory towards enhanced economic growth and welfare underscores its commitment to achieving sustainable development and prosperity for all citizens.